2014
DOI: 10.7874/kja.2014.18.2.58
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Monitoring Cisplatin-Induced Ototoxicity with Extended High-Frequency Pure-Tone Audiometry or Distortion-Product Otoacoustic Emission

Abstract: Background and ObjectivesTo compare the effectiveness of monitoring cisplatin-induced ototoxicity in adult patients using extended high-frequency pure-tone audiometry (EHF-PTA) or distortion-product otoacoustic emission (DP-OAE) and to evaluate the concurrence of ototoxicity and nephrotoxicity in cisplatin-treated patients.Subjects and MethodsEHF-PTA was measured at frequencies of 0.25, 0.5, 1, 2, 3, 4, 6, 8, 9, 11.2, 12.5, 14, 16, 18, and 20 kHz and DP-OAE at frequencies of 0.5, 0.75, 1, 1.5, 2, 3, 4, 6, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 27 publications
1
25
0
4
Order By: Relevance
“…Unfortunately, the number of ototoxic cases was not reported in all studies (69%). The median (mean) of observed ototoxic cases is 63% (57%), a value very similar to that found by us (62%). The criteria used for ototoxicity is not uniform because there is no universally accepted criterion for ototoxic change in DPOAE; nonetheless, several authors of articles from the last 5 years, including our study, used a threshold, particularly one suggested by Beattie et al for the DPOAE amplitude shift.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Unfortunately, the number of ototoxic cases was not reported in all studies (69%). The median (mean) of observed ototoxic cases is 63% (57%), a value very similar to that found by us (62%). The criteria used for ototoxicity is not uniform because there is no universally accepted criterion for ototoxic change in DPOAE; nonetheless, several authors of articles from the last 5 years, including our study, used a threshold, particularly one suggested by Beattie et al for the DPOAE amplitude shift.…”
Section: Discussionsupporting
confidence: 89%
“…With the exception of one article in which the data were not shown, in only three out of 17 articles was the observed shift in DPOAE levels not statistically significant after the first cycle. However, the ototoxicity of cisplatin was demonstrated in further cycles of these investigations . Additionally, in all studies listed in Table , in which DPOAE was measured after second and further cisplatin cycles, the presence of increased hearing impairment was registered.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, using each test in isolation may not be as effective as utilizing a test battery approach, as it increases the chances of obtaining reliable audiologic monitoring data over time. In addition, these two tests could be used to complement one another in every cycle of chemotherapy to ensure the earliest detection of ototoxicity [74]. …”
Section: Methodsmentioning
confidence: 99%
“…The damage starts at high-frequency coding cochlear base and progresses towards the apex. 19,20 In our study all children received treatment as per MCP841 protocol which include 12 doses of vincristine at a dose of 1.4 mg/m 2 between baseline and follow up evaluation and cranial irradiation of 1800cGy in those aged above 3 years. Antibiotics were selected at recommended doses depending on the clinical demands.…”
Section: Resultsmentioning
confidence: 99%